The Medical Law: The Hippocratic The Law and the Pseudo-Platonic Minos - Tieleman, Teun (Religion in the Roman empire, 2024)
This paper explores the notion of law (νόμος) as linked to medical competency in the Hippocratic tract The Law, including an isolated reference to 'the medical law' in the Hippocratic Oath (§ 2). It goes on to compare the role played by 'medical laws' in the pseudo-Platonic Minos or On Law. Building on the core meaning of 'law' as that which is accepted among a particular community, both treatises explain the medical law in terms of codified knowledge (as opposed to opinion or appearance, δόξα). This form of knowledge functions as a standard for professional identity and conduct. The question is raised as to which conclusions can be drawn from the resemblances and differences between the compared texts.